Characterization of Antibacterial Proanthocyanidins of Dalbergia monetaria, an Amazonian Medicinal Plant, by UHPLC-HRMS/MS - de Moura, Patricia Homobono Brito; de Sousa, Amaryllis Almeida; Porzel, Andrea; Wessjohann, Ludger A.; Leal, Ivana Correa Ramos; Martins, Roberto Carlos Campos (Planta Medica, 2020)
Dalbergia monetaria is an Amazonian plant whose bark is widely used to treat urinary tract infections. This paper describes a bio-guided study of ethanolic extracts from the bark and leaves of D. monetaria, in a search for metabolites active against human pathogenic bacteria. In vitro assays were performed against 10 bacterial strains, highlighting methicillin-sensitive Staphylococcus aureus and methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa. Fractioning of the extracts was performed using instrumental and classical techniques, and samples were characterized by UHPLC-HRMS/MS. Ethyl acetate fractions from bark and leaves showed similar antibacterial activities. EAFB is enriched in isoflavone C-glucosides and EAFL enriched in proanthocyanidins. Subfractions from EAFL presented higher activity and showed a complex profile of proanthocyanidins constructed by (epi)-cassiaflavan and (epi)-catechin units, including dimers, trimers and tetramers. The fragmentation pattern emphasized the neutral loss of cassiaflavan units by quinone-methide fission. Fraction SL7-6, constituted by (ent)-cassiaflavan-(ent)-cassiaflavan-(epi)-catechin isomers, showed the lowest MIC against the S. aureus and P. aeruginosa with values corresponding to 64 and 32 µg/mL, respectively. Cassiaflavan-proanthocyanidins have not been found previously in another botanical genus, except in Cassia, and the traditional medicinal use of D. monetaria might be related to the antibacterial activity of proanthocyanidins characterized in the species.
Keywords: Dalbergia monetaria; Leguminosae; antibacterial activity; proanthocyanidin; mass spectroscopy; methicillin-resistant Staphylococcus aureus; Pseudomonas aeruginosa